An atypical presentation of sinus mucopyocele in a pediatric cystic fibrosis patient - Horesh E (Dove Medical Press, 2015)
Elan Horesh, Andrew A Colin, Roy Casiano, Sara T WesterBascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USAAbstract: This case report details an association of chronic allergic conjunctivitis and respiratory tract colonization in a cystic fibrosis (CF) patient due to an ethmoidal mucocele infected with Escherichia coli. A 3-year-old CF patient presented for evaluation with complaints of chronic periocular erythema, conjunctival injection, and irritation for 2 years. He was treated for presumed allergic conjunctivitis with no improvement and continued to have overall worsening of symptoms on the right greater than the left eye in a waxing and waning pattern. On presentation to the Bascom Palmer Eye Institute, he was noted to have telecanthus and prominent erythema in the region of the medial canthus. Orbital imaging disclosed a mucocele in the right ethmoid sinus. The patient underwent functional endoscopic sinus surgery, with successful marsupialization of the ethmoidal mucocele, which was found on culture to be infected with E. coli. Post-operatively with continuous pulmonary care, the patient remains free of allergic conjunctivitis and E. coli colonization of the upper airway. This case highlights the importance of analyzing the adjacent sinus in patients with chronic, relapsing allergic conjunctivitis refractory to medical management, particularly in patients with underlying systemic diseases such as CF.Keywords: allergic conjuncitivitis, Escherichia Coli, cystic fibrosis, mucocele